Pengujian Konsumsi Energi Baterai pada Sepeda Motor Listrik Konversi Tipe Mid Drive 2 kW - Roza, Avifudin; Ismail, Andhi Akhmad; Kristianto, Daniel Janthinus (Badan Kerja Sama Teknik Mesin Indonesia, 2025)
A convertible electric motorcycle is a motorcycle that has undergone a change from a fuel-driven motor to an electric motor. When testing on a converted electric motorcycle, the battery indicator shows a significant decrease when passing an uphill track. This study aims to calculate battery energy consumption on a converted electric vehicle using a BLDC motor with a 2 kW mid drive type, both without and with the addition of internal gear. The process of testing and collecting data from battery energy consumption on a converted electric motorcycle is carried out by road tests on a flat track and a track that has an extreme climb. The test results on a converted electric motorcycle without the addition of internal gear with a distance of 100 meters on a flat road are 2,016 Wh, elevation 15° of 3,909 Wh, elevation 28° of 4,449 Wh, and elevation 40° of 5,059 Wh. While the test results of the converted electric motorcycle with the addition of internal gear on a horizontal track amounted to 2,421 Wh, elevation 15° of 4,240 Wh, elevation 28° of 5,528 Wh, and elevation 40° of 5,599 Wh.